2016
DOI: 10.1186/s40200-016-0275-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms involved in altered bone metabolism in diabetes: a narrative review

Abstract: Many studies have shown that change in metabolism caused by diabetes can influence the bone metabolism in a way that quality and strength of bone is decreased. A 6 times and 2 times increased risk of fracture is reported in patients with type 1 and type 2 diabetes, respectively. There are several mechanisms by which diabetes can affect the bone. The fact that some of these mechanisms are acting in opposite ways opens the door for debate on pathways by which diabetes affects the bones. On the other hand, bone i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 111 publications
(144 reference statements)
0
46
0
2
Order By: Relevance
“…In vitro studies have shown that high glucose weakened osteoblast response to 1,25(OH) 2 D 3 and indirectly down-regulated VDR expression (47). Likewise, our previous study also showed that high glucose attenuated the expression of insulin receptor and VDR, whereas these adverse effects can be reversed by 1,25(OH) 2 D 3 treatment (48).…”
Section: 25(oh) 2 D 3 Promotes Bone Formation With Foxo1 Inactivationmentioning
confidence: 66%
“…In vitro studies have shown that high glucose weakened osteoblast response to 1,25(OH) 2 D 3 and indirectly down-regulated VDR expression (47). Likewise, our previous study also showed that high glucose attenuated the expression of insulin receptor and VDR, whereas these adverse effects can be reversed by 1,25(OH) 2 D 3 treatment (48).…”
Section: 25(oh) 2 D 3 Promotes Bone Formation With Foxo1 Inactivationmentioning
confidence: 66%
“…Thus Ca:Ph ratio was increased. Rise of Ca:P in diet was proposed to prevent bone damage and upsurge intestinal Ca captivation in ovx rats (Ghodsi et al 2016). Contradicting to our data, Gopalakrishnan et al (2006) showed that serum ALP activity was amplified up to threefold in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…In rats with diabetes, osteocalcin and IGF-1 were significantly reduced. Studies showed that diabetes may lead to lower bone turnover index and impairment of both osteoblastic maturity and activity (Ghodsi et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Anyhow, in our study IGF-1 levels correlated with osteocalcin, suggesting a promoting action on osteoblast production. IGF-1 and OC show parallel patterns in different models in literature [28,29], however, studies about skeletal maturation suggest a triggering action on OC synthesis [30].…”
Section: Discussionmentioning
confidence: 99%